2023
DOI: 10.1093/ced/llad114
|View full text |Cite
|
Sign up to set email alerts
|

Does skin of colour education make a difference? A cross-sectional study at the University of Bristol

Abstract: At the University of Bristol, the dermatology curriculum was updated in 2020 to incorporate more teaching on skin of colour. In this article we summarise the findings of our cross-sectional study to establish whether improving teaching content on skin of colour results in a more confident cohort of students with better diagnostic skills in skin of colour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…A study from the University of Bristol, United Kingdom, showed that students who were exposed to the updated dermatology curriculum in 2020 (incorporating more teaching on SoC) compared to students who were not exposed to the updated dermatology curriculum were more confident and accurate in diagnosing conditions in SoC. 10 Hence, to address the existing disparity and educational deficiency, there is a need for medical curricula to incorporate comprehensive textual and visual materials that represent racial differences in dermatology. Addressing these educational disparities is crucial for ensuring equitable healthcare outcomes.…”
mentioning
confidence: 99%
“…A study from the University of Bristol, United Kingdom, showed that students who were exposed to the updated dermatology curriculum in 2020 (incorporating more teaching on SoC) compared to students who were not exposed to the updated dermatology curriculum were more confident and accurate in diagnosing conditions in SoC. 10 Hence, to address the existing disparity and educational deficiency, there is a need for medical curricula to incorporate comprehensive textual and visual materials that represent racial differences in dermatology. Addressing these educational disparities is crucial for ensuring equitable healthcare outcomes.…”
mentioning
confidence: 99%